Finite element analysis of dynamic progressive failure of plastic composite laminates under low velocity impact. (1st January 2017) - Liao, B.B.; Liu, P.F.
Abstract: This paper studies dynamic mechanical responses and damage mechanisms of plastic fiber-reinforced polymer matrix composite laminate under low velocity impact. First, the plastic damage model is introduced for intralaminar damage, where Puck's failure criteria and strain based damage evolution laws for fiber and matrix are used, and the bilinear cohesive model is adopted for delamination. Second, an uncoupled numerical scheme for dealing with the intralaminar plastic deformation and damage evolution by finite element analysis (FEA) is originally proposed based on the strain equivalence hypothesis, in which the effective stresses and strains are first solved using the backward Euler algorithm and then the nominal stresses and damage variables are updated independently. Finally, the proposed algorithm is implemented using ABAQUS-VUMAT by the time stepping algorithm. For two composite specimens under transverse impact, the impact force-time curve, the impact displacement-time curve and the dissipated energy at different impact energies are studied by comparing the results using experiments and FEA. Numerical results show the plastic damage model leads to higher precision than the elastic damage model as the impact energy becomes relatively large.